Weather forecast on TV: individual style of presenters - Hidzun Olha (My University, 2021)
The aim of the work is to establish the types of language identities in weather forecast on TV and analysis of the speech behavior and individual style of British and American TV weather presenters. The object of this study is the individual style and language identity of English-speaking TV presenters of weather forecasts. The subject of this study is lexical, grammatical and pragmatic features of the speech of weather presenters broadcast on the TV channels in the UK and USA.
Keywords: Weather forecast; english-speaking TV